PREVALENCE OF DRY EYE IN CHILDREN AGED 5 TO 15 YEARS AND ITS PATTERN WITH DURATION OF SCREEN TIME IN THE EASTERN PART OF BIHAR - ANTARYAMI SHARMA; REENA KUMARI; DINESH KUMAR BHAGAT (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Dry eye disease (DED) is increasingly recognized as a significant health problem in children, particularly about screen time exposure. However, detailed epidemiological data on DED in young populations, especially in regions such as Eastern Bihar, are sparse. This study aims to assess the prevalence of DED among children aged 5–15 years and explore the relationship between the duration of screen time and the occurrence of DED. Methods: A cross-sectional study at M.G.M. Medical College and L.S.K. Hospital, Kishanganj, Bihar, examined 140 children with DED symptoms. Diagnostic tests such as tear film breakup time and Schirmer’s test were conducted during comprehensive ocular examinations. The association between DED prevalence and parental and self-reported screen usage was examined. Results: The prevalence of DED among the participants was 12.1%. There was a significant association between higher screen time and increased prevalence of DED, with the severity of symptoms correlating positively with a longer duration of screen exposure. Children with severe DED reported significantly more screen time compared to those with milder forms. Conclusion: The study confirms a notable prevalence of DED among children in Eastern Bihar, closely linked to excessive screen time. These findings highlight the need for public health strategies to manage screen exposure in children to prevent the onset of DED.